Evaluation of age variation changes in cervical vertebrae: 2-Dimensional (2D) geometric morphometrics approach - Muhammad Faiz Mohd Fauad; Ku Mastura Ku Mohd Noor; Aspalilah Alias; Ker Woon Choy; Wei Lin Ng; Eric Chung; Yuan Seng Wu; Noraina Hafizan Norman (Elsevier, 2024)
Indexed by Scopus